Radiological characteristics of COVID-19 patients and correlation of chest CT severity index with different clinical forms of disease in SKIMS medical college and hospital Kashmir, India - Bashir, Shazia; Mir, Mohammad Farooq; Salroo, Imran; Naik, Muzaffar Ahmad (International Journal of Advances in Medicine, 2021)
Background: The objective of this paper was to study the radiological characteristics of COVID-19 patients and to establish a possible correlation of chest CT severity index (CTSI) with different clinical forms of disease. Methods: All the patients who routinely underwent non contrast CT chest and tested positive for COVID-19 by RT-PCR of respiratory secretion obtained by broncho alveolar lavage and nasopharyngeal swab test had been included in the given study. The collected data was analyzed to find a possible correlation of chest CTSI with different clinical forms of disease. Results: COVID-19 patients reflected some interesting radiological features like ground glass opacity (GGO) in (90.1%) followed by consolidation in (70.4%) patients. However, (67.6%) patients reflected both GGO and consolidation features. Peripheral distribution was most common in patients accounting for (90.1%) versus (60.6%) with central distribution but (60.6%) had both peripheral and central distribution. We observed that there is significant correlation (p value <0.001) between severity of disease as per oxygen saturation level and severity of disease on the basis of CTSI. Conclusions: We concluded that COVID-19 pneumonia patients significantly exhibit some radiological features that include GGO and consolidation with peripheral and central distribution. Therefore in addition to other clinical parameters CT severity score can be treated as a reliable diagnostic tool to determine the severity status of disease.